2015
DOI: 10.1007/s10549-015-3489-x
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime physical activity and risk of breast cancer in pre-and post-menopausal women

Abstract: To investigate the association between different types of physical activity (PA) and breast cancer. A case-control study of breast cancer was conducted in Western Australia from 2009 to 2011, in which 1205 women with breast cancer and 1789 frequency age-matched breast cancer-free control women were recruited. A self-administered questionnaire was used to collect information about lifetime and age-period recreational, household, occupational and transport physical activities. Detailed questions about demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…In our study, physical activity was associated with a risk reduction of BC; this confirms the results of prospective studies in the world [ 51 โ€“ 53 ]. Conversely, studies conducted in Los Angeles and Western Australia, found the opposite or non-significant effect of physical activity with BC [ 54 , 55 ]. Our results could be explained by the fact that majority of Central African women do not use modern conveniences (car, machines, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In our study, physical activity was associated with a risk reduction of BC; this confirms the results of prospective studies in the world [ 51 โ€“ 53 ]. Conversely, studies conducted in Los Angeles and Western Australia, found the opposite or non-significant effect of physical activity with BC [ 54 , 55 ]. Our results could be explained by the fact that majority of Central African women do not use modern conveniences (car, machines, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The full methods have been described previously. (6) Briefly, participants were between two and four years post-diagnosis, between 18 and 80 years of age and residing in WA at the time of diagnosis, and had previously taken part in a case-control study (13). Breast cancer survivors who were currently receiving chemotherapy or radiotherapy, had experienced a recurrence of their breast cancer, or had been diagnosed with another cancer were ineligible.…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiologic case-control studies have produced inconsistent results. Some have reported that high levels of occupational physical activity are associated with a reduced risk of breast cancer [3-19], whereas others have found an opposite or non-significant effect [20-28]. Few prospective studies have evaluated the association between occupational physical activity and breast cancer risk.…”
Section: Introductionmentioning
confidence: 99%